Pengaruh Prestasi Belajar Pendidikan Agama Islam Terhadap Perilaku Disiplin Siswa Kelas X SMK Muhammadiyah Panekan Kabupaten Magetan Tahun Pelajaran 2015/2016 - Sugama, Teguh Yoga, Drs. Zaenal Abidin M.Pd (2017)
Islamic Religious Education (PAI) is given as a subject in school with the hope that it can produce learners who really have a strong faith and high devotion based on noble character, so it can be implemented in everyday life. Through Islamic education in school students are expected to be a good person, has a strong personality and a healthy mental attitude and morals behavior that is commendable. The formulation of the problem studied is: is there any influence of learning achievement of Islamic Religious Education on student behavior ?. The purpose of this research is to know the influence of Islamic education achievement on student behavior. This research includes descriptive research type with quantitative approach. The population in this research is all students of class X SMK Muhammadiyah Panekan academic year 2015/2016. The sample of this research is all students of class X of Marketing SMK Muhammadiyah Panekan academic year 2015/2016 which amounted to 25 students or can be called population research. Methods of data collection using questionnaires and documentation. Methods of data analysis using correlation analysis. The result of data analysis shows that there is influence of PAI learning achievement toward student behavior. Evident from result of quantitative data analysis with correlation analysis which get rxy value bigger than rtabel that is 0,757> 0,396 at level of trust 5%. This means that the higher the PAI learning achievement, the better the students' behavior. Conversely, the lower the PAI learning achievement, the less good the student behavior. Thus the proposed hypothesis which reads: "There is influence of learning achievement of Islamic education on discipline behavior of students of class X SMK Muhammadiyah Panekan" has been proven. Research conclusions are: there is influence of learning achievement of PAI toward behavior of student of Class X SMK Muhammadiyah Panekan Year Lesson 2015/2016.